MicroRNA-27a alleviates LPS-induced acute lung injury in mice via inhibiting inﬂammation and apoptosis through modulating TLR4/MyD88/NF-κB pathway - Ju, MinJie; Liu, BoFei; He, HongYu; Gu, ZhunYong; Liu, YiMei; Su, Ying; Zhu, DuMing; Cang, Jing; Luo, Zhe (Cell cycle (Georgetown, Tex.), 2018)
Acute lung injury (ALI) is a critical clinical condition with a high mortality rate, characterized with excessive uncontrolled inflammation and apoptosis. Recently, microRNAs (miRNAs) have been found to play crucial roles in the amelioration of various inflammation-induced diseases, including ALI. However, it remains unknown the biological function and regulatory mechanisms of miRNAs in the regulation of inﬂammation and apoptosis in ALI. The aim of this study is to identify and evaluate the potential role of miRNAs in ALI and reveal the underlying molecular mechanisms of their effects. Here, we analyzed microRNA expression profiles in lung tissues from LPS-challenged mice using miRNA microarray. Because microRNA-27a (miR-27a) was one of the miRNAs being most significantly downregulated, which has an important role in regulation of inflammation, we investigated its function. Overexpression of miR-27a by agomir-27a improved lung injury, as evidenced by the reduced histopathological changes, lung wet/dry (W/D) ratio, lung microvascular permeability and apoptosis in the lung tissues, as well as ameliorative survival of ALI mice. This was accompanied by the alleviating of inflammation, such as the reduced total BALF cell and neutrophil counts, decreased levels of tumor necrosis factor alpha (TNF-α), interleukin-1 (IL-6) interleukin-1β (IL-1β) and myeloperoxidase (MPO) activity in BAL fluid. Toll-like receptor 4 (TLR4), an important regulator of the nuclear factor kappa-B (NF-κB) signaling pathway, was identified as a novel target of miR-27a in RAW264.7 cells. Furthermore, our results showed that LPS stimulation increased the expression of MyD88 and NF-κB p65 (p-p65), but inhibited the expression of inhibitor of nuclear factor-κB-α (IκB-α), suggesting the activation of NF-κB signaling pathway. Further investigations revealed that agomir-miR-27a reversed the promoting effect of LPS on NF-κB signaling pathway. The results here suggested that miR-27a alleviates LPS-induced ALI in mice via reducing inﬂammation and apoptosis through blocking TLR4/MyD88/NF-κB activation.